TYPES OF FUNCTIONAL STYLES IN ENGLISH (Journal of Universal Science Research, 2025)
The taxonomy and linguistic characteristics of the English language's functional styles are the main topics of this essay. Effective communication requires functional styles, which modify language to fit particular audiences and goals. The study examines and analyzes the distinctive language characteristics of scientific, official, journalistic, colloquial, and literary styles. Important elements including syntax, stylistic devices, and vocabulary selection are analyzed to show how they influence communication. The purpose of this thorough research is to emphasize the importance of functional styles in comprehending stylistics and enhancing language usage.